Efficient wound odor removal by β‐cyclodextrin functionalized poly (ε‐caprolactone) nanofibers. Issue 45 (13th August 2015) - Narayanan, Ganesh; Ormond, Bryan R.; Gupta, Bhupender S.; Tonelli, Alan E.
ABSTRACT Polymer‐cyclodextrin (CD) composite nanofibers, by virtue of the hollow cavities and abundant hydroxyl groups present in CDs, have tremendous potential in a variety of biomedical applications. However, in most cases, especially in aliphatic polyesters, polymer chains thread readily into CD cavities, therefore its potential has not yet been fully realized. Herein, we report the formation of poly(ε‐caprolactone) (PCL)/β‐CD functional nanofibers by electrospinning their mixture from chloroform/N, N‐dimethylformamide (60 : 40). The fiber diameters of the neat PCL and β‐CD functionalized fibers were measured from the images obtained from a scanning electron microscope and were found to be about 500 nm. The efficiency of wound odor absorbance by these composite fibers was studied using a simulated wound odor solution, consisting of butyric and propionic acids in ethanol. Immersion tests indicated that even under less than ideal test conditions, the nanofibers containing β‐CDs were very efficient in masking the odor. The odor masking capability of the β‐CD functionalized PCL nanofibers were further confirmed by thermogravimetric analyses and GC observations, with the former method showing unique degradation patterns. The PCL/β‐CD nanocomposites, by virtue of having their β‐CD cavities free and unthreaded by PCL, could potentially be an ideal substrate for removing wound odors through formation of inclusion compounds with odorants, while providing an ideal environment for the wound to heal. These results suggest tailoring polymer‐CD nanostructures for specific applications in wound odor absorbance, surface grafting of chemical moieties, and vehicles for drug delivery, as examples. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42782.